Studi Etnofarmasi dan Skrining Fitokimia Ekstrak Kulit Batang Tumbuhan Nelambo Suon (Rubiaceae) Obat Tradisional Antimalaria Suku Yali di Distrik Heriapini Kabupaten Yahukimo - Tomi A. Nelambo; Linus Y. Chrystomo; Lisye I. Zebua (Jurnal Biologi Papua, 2022)
The Nelambo Suon plant is an antimalarial medicinal plant belonging to the Rubiaceae family. This plant is commonly used as a traditional medicine by the Yali Tribe, Sabelebi Village, Heriapini District, Yahukimo Regency, Papua. This plant is typical of Papua which grows wild in hilly habitats and on the edge of cliffs in tropical rain climates. The purpose of this study was to determine the benefits of the traditional antimalarial medicinal plant of the Suon based on ethnopharmaceutical studies and to determine the content of secondary metabolite chemical compounds through the bark extract of Suon Nelambo. The method used to determine the benefits of plants in ethnopharmaceuticals is interviews method. While the test for the content of chemical compounds of secondary metabolites used the phytochemical screening method according to Farnsworth. The results showed that the Suon plant has long been used for generations by the Yali tribe in Sabelebi Village as a traditional antimalarial medicine. The part of the plant organ used is the bark of the stem, which is young or still soft and not too hard. How to use it is by boiling, and the boiled water is drunk in the morning and evening for a period of 3-5 days. The results of phytochemical screening showed that the bark extract of Suon contains a group of secondary metabolite chemical compounds, such as alkaloids, flavonoids, steroids, triterpenoids, saponins, tannins and quinones. The results of this study are one of the new discoveries of medicinal plants that can be used as antimalarial drugs in Papua. Key words: ethnopharmacy; phytochemical screening; Nelambo Suon; Yahukimo.